2018
DOI: 10.1002/adem.201700995
|View full text |Cite
|
Sign up to set email alerts
|

Surface Textures Fabricated by Laser Surface Texturing and Diamond Cutting – Influence of Texture Depth on Friction and Wear

Abstract: In the present work, the authors study the tribological characteristics of textured stainless steel surfaces with different texture depths ranging from 1.3 to 23 mm created by laser surface texturing and ultra-precision diamond cutting. The periodicity of the surface textures is kept constant at 90 mm for each fabrication technique and texture depth. Subsequent ball-on-disk friction tests show that friction and wear can be effectively reduced by the surface texturing. It is found that the effectiveness of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 37 publications
(30 reference statements)
0
22
0
Order By: Relevance
“…The surface enhanced Raman scattering (SERS) measurement is also conducted with the machined ordered micro/nanostructures. 5…”
Section: Introductionmentioning
confidence: 99%
“…The surface enhanced Raman scattering (SERS) measurement is also conducted with the machined ordered micro/nanostructures. 5…”
Section: Introductionmentioning
confidence: 99%
“…The laser surface texturing operation process is simple, non-toxic, non-polluting, high stability, and can handle a wide variety of materials, which has great advantages in superhydrophobic surface preparation [13,14]. In the research that has been carried out, most of the work uses picosecond and femtosecond lasers [15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Surface texturing is a promising approach aiming at modifying friction and wear properties by introducing well‐defined textures. It is well‐known that precisely defined and well‐selected textures are able to build‐up a hydrodynamic pressure, to store lubricant and/or wear particles as well as to reduce the real contact area, thus beneficially affecting friction and wear in different lubrication regimes . Apart from a potential friction and wear reduction, it has been reported that friction can be increased by surface texturing when using properly selected structural parameters …”
Section: Introductionmentioning
confidence: 99%
“…Apart from structural parameters, several studies have pointed out that the texture's shape has a tremendous impact on the resulting frictional behavior under dry and lubricated conditions . In order to fabricate well‐defined surface textures, a broad range of methods including embossing, etching, laser‐based technologies, and diamond cutting can be used. In this context, laser surface texturing (LST) has proven to be a powerful technique to fabricate periodic surface textures with feature sizes on the micron scale with a high precision, accuracy and homogeneity on various materials …”
Section: Introductionmentioning
confidence: 99%